Multifaced therapies in the care of children with Autism Spectrum Disorder - A literature review - Sztybór, Mateusz; Nowak, Gabriela; Głogowska, Karen; Piątkiewicz, Julia; Żmijewska, Aleksandra; Maleszewska, Monika; Krzyżanowska, Maria; Wojtas, Mikołaj; Kapica, Marcin; Kopacz, Wojciech (Journal of Education, Health and Sport, 2024)
Autism is an abnormality in functioning that influences how people interact with others, communicate, learn new things and behave. According to the WHO, autism already occurs in 1 in 100 children. Although it affects people of all ages it is mostly diagnosed in children. This makes the essence of autism management to support the child’s development. Autism Syndrome Disorder (ASD) has become a target of research and interest in modern medicine, especially psychiatry pediatrics and psychology. Help and support during the development of a child with ASD have big influence in alleviating symptoms and developing functioning. The multitude of modern therapies makes it available to provide comprehensive care for the child. According to a recent analysis, therapies such as music therapy have positive effects. They can boost a child’s communication, interpersonal, social and language skills. They improve the child’s overall functioning which converts into his quality of life in adulthood. The profits of occupational or individual therapies are a new case in the context of people with ASD. It requires more extensive randomized studies, but it offers great hope and optimism for the improvement of therapies and a multifaceted support system for children with ASD.